Sekolah Unggul: Persepsi Siswa Terhadap Mutu Pendidikan SDIT ATTIN Kota Pariaman Sumatera Barat - Yulmaidar Yulmaidar; Roni Putra; M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2023)
Excellent schools are often juxtaposed with the quality of education organised by an educational institution (school). An excellent school is something that every school in Indonesia aspires to. Because by holding a Superior School, the school becomes the target of the surrounding community. This study aims to describe students' perceptions of the implementation of education organised by SDIT ATTIN. This type of research is survey research. The sample of this research is grade 4 to grade 6 students. The sample was taken randomly as many as 26 students. The instrument used is a questionnaire. The questionnaire was made by the researcher. The questionnaire uses a Likert scale. The Likert scale used is a Likert scale with intervals of 1-4. The weight of four indicates very good (SB), three for good (B), two for good enough (CB), and one for less good (KB). Furthermore, the data obtained from the questionnaire is processed to be the average value. The results of the percentage processing were then analysed and grouped into superior, good, good enough and less good criteria. Based on the research results obtained: (1) The quality of SDIT ATTIN graduates is very good or superior, (2) The quality of the learning process at SDIT ATTIN is also superior, (3) The quality of SDIT ATTIN teachers is good, and (4) the managerial quality of SDIT ATTIN is also superior. Thus SDIT ATTIN can be categorised as a superior school. Keywords: School excellence, student perceptions, Quality of Education, SDIT ATTIN